Communication of Rituals and Traditional Ceremonies Dayak Ngaju Community in Central Kalimantan - Kurniawati, Dwi Putri Mishari; Hastjarjo, Sri; Slamet, Yulius (PT FORMOSA CENDEKIA GLOBAL, 2024)
Dayak Ngaju community, traditional rituals, and ceremonies cannot be separated. This research is essensial because no research summarized the traditional rituals and ceremonies of the Dayak Ngaju community using a communication science approach. The theory of Prayer as Rhetoric initiated by William Fitzgerald is the basis for this study. Use qualitative research Miles and Huberman's interactive model through data process, collection, reduction, display, and conclusions. This study describes 4 (four) traditional rituals and ceremonies held by the Dayak Ngaju community such as traditional wedding ceremonies, nyaki tihi ceremonies, farming rituals, and laluhan ceremonies. The result is Dayak Ngaju community in Kuala Kapuas Regency holds traditional ceremonies and rituals as a form of communication with The Creator with the aim of petition, thanksgiving, and confession completed by meaningful symbols.